2020
DOI: 10.1002/cssc.202002660
|View full text |Cite
|
Sign up to set email alerts
|

More Than Just a Reagent: The Rise of Renewable Organohydrides for Catalytic Reduction of Carbon Dioxide

Abstract: Stoichiometric carbon dioxide reduction to highly reduced C1 molecules, such as formic acid (2e−), formaldehyde (4e−), methanol (6e−) or even most‐reduced methane (8e−), has been successfully achieved by using organosilanes, organoboranes, and frustrated Lewis Pairs (FLPs) in the presence of suitable catalyst. The development of renewable organohydride compounds could be the best alternative in this regard as they have shown promise for the transfer of hydride directly to CO2. Reduction of CO2 by two electrons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 152 publications
(374 reference statements)
0
6
0
Order By: Relevance
“…In particular, hydride and H atom transfer reactions are important in, for example, catalytic hydrogenation, hydroformylation, or small molecule activation reactions relevant to renewable energy storage. This has stimulated extensive research on hydride and H atom donor reagents, metal and nonmetal containing, as reducing agents during the past decades. Inspired by natural enzymatic cofactors, for example, nicotinamide adenine dinucleotide phosphate (NADPH) or flavin adenine dinucleotide (FADH 2 ), several nonmetal hydride donors with dihydropyridines or dihydroquinoline moieties have been established . FADH 2 acts as a hydride donor in various biochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, hydride and H atom transfer reactions are important in, for example, catalytic hydrogenation, hydroformylation, or small molecule activation reactions relevant to renewable energy storage. This has stimulated extensive research on hydride and H atom donor reagents, metal and nonmetal containing, as reducing agents during the past decades. Inspired by natural enzymatic cofactors, for example, nicotinamide adenine dinucleotide phosphate (NADPH) or flavin adenine dinucleotide (FADH 2 ), several nonmetal hydride donors with dihydropyridines or dihydroquinoline moieties have been established . FADH 2 acts as a hydride donor in various biochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Later, [CpFe­[CO) 2 ] 2 in the presence of an excess of P n Bu 3 was shown to catalyze the N -formylation of amines with CO 2 and PhSiH 3 at mild temperatures and in high yields . Our catalyst design was inspired by these results and previous work, which showed that iron­(II) NHC complexes efficiently activate CO bonds, including catalytic hydrosilylation of carbonyl and ester functionalities, and the catalytic polymerization of lactones. In the course of our work, we also identified an iron hydride upon exposure of an NHC iron complex to PhSiH 3 , a species that has often been inferred as key intermediate in the activation of CO 2 . , Due to these reactivity patterns, we were interested in exploring the activity of such iron NHC complexes as catalysts for the activation and functionalization of CO 2 . Here we show that these complexes are indeed useful in this catalytic CO 2 fixation, and we provide support that the active species is the actual NHC iron species rather than dissociated NHC ligand, even though the NHC on its own is an excellent catalyst for CO 2 activation and the N -formylation of amines .…”
Section: Introductionmentioning
confidence: 69%
“…Organoboranes, characterized by a C-BR 2 group, were first discovered as classic precursors for C–OH hydroxy groups in the early 20th century. Organoboranes have been widely used for Suzuki–Miyaura C–C coupling in organic chemistry. It is undeniably true that the discovery of Suzuki–Miyaura cross-coupling of aryl halides and organoboranes represented a milestone in C–C bond formation history, which was honored with Nobel Prize in 2010. Since then, the new era of organoboranes began. Among them, diboranes, with the formula of (RO) 2 B–B­(OR) 2 , are the common borylation reagents in all kinds of organic reactions. Two most commonly used diboranes are B 2 (OH) 4 and bis­(pinacolato)­diborane (B 2 pin 2 ).…”
Section: Synthesis Of Diboranesmentioning
confidence: 99%